Effects of psychological reactance on emotional experience: Evaluations of a cartoon - Imajo, Shuzo (The Japanese Journal of Psychology, 1984)
In this paper, it was examined whether resistance to persuasion due to reactance could occur in emotional experience. After reading another male subject's (fictitious) message about a cartoon, the subject saw the cartoon in question, and evaluated it. The contents of the message were varied in order to manipulate strength of threat to emotional freedom. The low threat message was simply a statement of personal impression of the cartoon, on the other hand, the high threat message was worded so as to force the subject to experience pleasant emotions. In Experiment I, some sex differences were obtained. Toward the male coercive communicator, female subjects complied strongly, but male subjects rather showed weak resistance. In Experiment II, male subjects were forced to experience pleasant (or unpleasant) emotions. The results of funniness ratings showed that persuasiveness of the messages reduced in the high threat conditions regardless of the positions advocated. Additionally, subjective responses to reactance arousal were obtained in both experiments. These results suggested that reactance theory could also be applied to emotions.